Epiploic Appendagitis. Issue 10 (October 2015) - Redmond, Paul; Sawaya, David E.; Miller, Kristen H.; Nowicki, Michael J.
<x xml:space="preserve">Abstract</x> Abstract A 9-year-old boy presented with acute onset of abdominal pain and vomiting. History, physical examination, and initial laboratory testing failed to provide a diagnosis. A computed tomography scan revealed the rare finding of epiploic appendagitis. We review the literature of this rare, but increasingly recognized, condition that mimics appendicitis and needs to be considered in the child with acute abdominal pain.